The Relationship Between Protein Whey Milk Consumption and The Occurrence of Acne Vulgaris in Adolescents Aged 18-21 Years - Timotius, Timotius; Charity Kamalo, Angelica Joana; Eunike, Debora; Titanic, Pussof Yayazucah; Priyanto, Teguh; Ã‡elik, Semih (Jurnal Kesehatan, 2023)
Acne vulgaris is an inflammation that occurs in the pilosebaceous gland with a prevalence of 18-21 years affected adolescents. This study aimed to determine the relationship between consumption of whey protein and the incidence of acne vulgaris. The research design was a literature review by searching medical scientific articles. Over 7,408 articles were found when searching for "protein" and "acne vulgaris." The articles were sorted by relevant publication in the last five years. There were 2,179 pertinent articles, which were then excluded from book studies that read 581 articles. Then, articles were screened only for whey protein research in the form of milk, so the remaining 129 studies were continued by selecting only subjectsâ€”adolescents aged 18-21 years so that the remaining 20 relevant articles are summarized in this study. The literature review results show a significant relationship between protein consumption and the incidence of acne vulgaris. The increase in sebum production caused by high protein consumption is the main reason for this correlation. Research findings suggest that people who consume high amounts of whey protein are more likely to develop acne vulgaris. In conclusion, this study lost the importance of nutrition in the incidence of acne vulgaris, with whey protein consumption being a significant contributing factor. The findings of this study may benefit individuals who wish to prevent or treat acne vulgaris by making dietary changes. Further research is needed to determine the optimal amount of protein intake to minimize acne vulgaris.